Islam dan Nyadran di Kendal Sinkronisasi Ajaran Islam dan Adat Lokal: Tinjauan Kritis Terhadap Tradisi Nyadran (Sedekah Laut) di Pantai Sendang Sikucing Kecamatan Rowosari Kabupaten Kendal dalam Perspektif Pendidikan Islam dan Budaya Jawa - Miftachul Richaniah; Muhammad Ahsanul Husna; Nurul Azizah (Universitas Hamzanwadi, 2026)
This research aims to critically analyze the synchronization process between Islamic theological values ​​and local wisdom in the Nyadran (Sea Almsgiving) tradition on Sendang Sikucing Beach, Kendal Regency. The main problem studied is the tension between the formal-normative theological perspective which is concerned about shirk and the cultural practices of fishing communities which view this ritual as an expression of gratitude. This research uses a qualitative approach with the type of field research. Data was collected through participatory observation, documentation, and in-depth interviews with religious leaders, traditional leaders and fishing communities. Data analysis was carried out through reduction stages, data presentation and drawing conclusions. The research results show that the Nyadran tradition at Sendang Sikucing Beach is a manifestation of intelligent acculturation that uses the